Analisis Miskonsepsi Siswa Berbantuan Certainty of Response Index (CRI) pada Materi Pembelajaran Laju dan Orde reaksi (Jurnal Inovasi Pendidikan Kimia, 2023)
Misconceptions show because there is a concept that is not in accordance with the actual concept. The purpose of this study is to find out the misconceptions experienced by class XI students in the material rate and order of reaction with certainty of response index (CRI). Then to be able to find out the cause of the misconception in class XI students in understanding the concept of rate and order of reaction by using the Certainty of Response Index (CRI) method. This type of research is qualitative research with a descriptive approach. This research was conducted at SMA Negeri 1 Lempuing class XI of the 2020/2021 school year at the OIC lempuing. Instruments used test sheets, student questionnaires and interview sheets. The results of the analysis of research data showed that there are learners who understand 15%, misconception level 1 in learners with a percentage of 56%, misconceptions of level 2 with a percentage of 4%. While students who do not understand get a percentage of 35%. Aspects of the causes of the misconception of learners are the factors of learners themselves, factors in the use of learning methods and textbook factors that there are many errors.